DEMOGRAPHIC EXPLORATION OF ACADEMIC SELF-EFFICACY BELIEFS OF SELECTED SENIOR SECONDARY SCHOOL STUDENTS IN OGBOMOSO AREA OF OYO STATE - Akanbi, S. T. (Sokoto Educational Review, 2019)
This study aimed at exploring academic self-efficacy beliefs of Senior Secondary School students using some demographic variables. The study adopted a descriptive survey research design. Two hundred and seventy-nine (279) students randomly selected from selected Senior Secondary Schools in Ogbomoso area of Oyo State participated in the study. The instrument used for r the study was the Students’ Academic Efficacy Scale with reliability co-efficient of 0.76. Subjecting the data collected to statistical analysis, student t-test was used. Four hypotheses were tested at 0.05 level of significance. The results showed that male students were more self-efficacious than their female counterparts. Also, the students who are older than being in secondary school (especially SS 1 & SS2), aged 17 years and above had lower self-efficacy than students aged 17 years and below. However, significant difference did not occur among the students based on subject combinations and parental educational qualifications. The outcomes of the study were fully discussed and suggestions were made for further studies.